2017
DOI: 10.21037/jtd.2017.10.94
|View full text |Cite
|
Sign up to set email alerts
|

Short and long-term results of sternectomy for sternal tumours

Abstract: Background: We analyzed our experience in sternal resections (SRs) for primary or secondary neoplasm focusing on technical aspects of reconstruction, post-operative outcomes and long term survival. Methods: From January 2005 to December 2015, 36 patients (24 males, 67%) underwent surgical excision of primary (chondrosarcoma n=18 patients, 50%; osteosarcoma n=2, 6%; Ewing sarcoma n=1, 3%; other n=2, 6%) or secondary (breast cancer n=7, 19%; kidney carcinoma n=2, 6%) sternal tumour. We performed n=30 partial ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 24 publications
(61 reference statements)
1
24
2
Order By: Relevance
“…Partial or total sternectomy for solitary metastatic sternal deposits is well established with relatively low morbidity, mortality and improvement in quality of life and long-term survival [ 7 ]. Interestingly, the aspect of chest wall or sternal pain is one aspect that considerably improves following sternal metastasectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Partial or total sternectomy for solitary metastatic sternal deposits is well established with relatively low morbidity, mortality and improvement in quality of life and long-term survival [ 7 ]. Interestingly, the aspect of chest wall or sternal pain is one aspect that considerably improves following sternal metastasectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Overall 5-year survival rate in the chondrosarcoma group was 80%. Bongiolatti et al (13) reported 36 sternal resection and reconstruction, 50% of which for chondrosarcoma. Reconstruction was made using the STRATOS system combined with a muscle flap and/or PTFE (30.5%), ePTFE patch (16.7%), and bilateral pectoralis major myocutaneous advancement flaps (52.7%).…”
Section: Reconstructive Techniquesmentioning
confidence: 99%
“…Holden first described partial sternectomy for a primary sarcoma in 1878 [3] and the first complete sternectomy was performed by Brodin and Linden in 1959 [4]. Sternal resection with immediate reconstruction of the anterior chest wall defect was recommended for both primary and secondary sternal tumors as curative treatment [5].…”
Section: Introductionmentioning
confidence: 99%